2015
DOI: 10.1186/s12967-015-0411-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of SLMAP genetic variants in susceptibility of diabetes and diabetic retinopathy in Qatari population

Abstract: BackgroundOverexpression of SLMAP gene has been associated with diabetes and endothelial dysfunction of macro- and micro-blood vessels. In this study our primary objective is to explore the role of SLMAP gene polymorphisms in the susceptibility of type 2 diabetes (T2DM) with or without diabetic retinopathy (DR) in the Qatari population.MethodsA total of 342 Qatari subjects (non-diabetic controls and T2DM patients with or without DR) were genotyped for SLMAP gene polymorphisms (rs17058639 C > T; rs1043045 C > T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…This trend has changed over the last 50 years. Females were more likely to be diagnosed with T2DM in recent years, associated with increasingly sedentary lifestyles and high energy, carbohydrate fatty diets . Consistent with prior studies, the current investigation found that African Americans and Hispanics were more likely to have an onset of T2DM than Caucasians in the Medicare population …”
Section: Discussionsupporting
confidence: 87%
“…This trend has changed over the last 50 years. Females were more likely to be diagnosed with T2DM in recent years, associated with increasingly sedentary lifestyles and high energy, carbohydrate fatty diets . Consistent with prior studies, the current investigation found that African Americans and Hispanics were more likely to have an onset of T2DM than Caucasians in the Medicare population …”
Section: Discussionsupporting
confidence: 87%
“…This trend has changed over the last 50 years. Previously, females were more likely to have diagnosed T2DM, but in recent years, the increasing sedentary lifestyle of males is attributed to their increased prevalence of T2DM (28, 29). In line with these studies the current study found that females were more likely to have a T2DM “remission” compared to males.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, some screened hub genes were common, like CNN1 , an actin filament-associated regulatory protein expressed in smooth muscle and many types of non-muscle cells(Liu and Jin, 2016 ), and CCDC 34 , involved in bladder carcinoma pathogenesis (Gong et al, 2015 ) and non-small-cell lung cancer (Petroziello et al, 2004 ). Nevertheless, we found some other different hub genes, e.g., SLC20A1 , involved in vascular smooth muscle cell calcification (Wu et al, 2016 ) and calcific aortic valve disease (El Husseini et al, 2013 ); MAD2L2 , a component of the mitotic spindle assembly checkpoint and a crucial contributor to the control of DNA repair activity (Boersma et al, 2015 ); UBE2T , a ubiquitin-conjugating enzyme (E2) essential for Fanconi anemia and prostate cancer (Machida et al, 2006 ; Wen et al, 2015 ); SLMAP , associated with Brugada syndrome and diabetes (Ishikawa et al, 2012 ; Upadhyay et al, 2015 ); GALK1 , a major enzyme for the metabolism of galactose (Sangiuolo et al, 2004 ); GINS2 , a complex essential in the initiation of DNA replication and progression of DNA replication fork (Liang et al, 2016 ). Additionally, role for FAM198B in AAD is hitherto unknown.…”
Section: Discussionmentioning
confidence: 99%